(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article analyzes information on the botanical description, chemical composition, use for diseases, preparations and agrotechnology of the medicinal plant Taraxacum officinalis L. The flowers and leaves of the plant contain taraxanthin, flavoxanthin, vitamins C, A, V2, E, PP, choline, saponins, resins, manganese salts, iron, calcium, phosphorus, up to 5% protein, which make nutritious food. The dried roots contain triterpene compounds. The seeds of the plant ripen in early July and are harvested. 3-4 kg of seeds are used per hectare.